Some Observations on Teleost Respiration with Emphasis on the Gill Filament Musculature and the Respiratory Centres of the Brain - Aimer, Valerie (My University, 1961)
Two aspects of teleost respiration have been emphasised in this investigation. Firstly the gill filaments themselves were observed in order to determine whether or not they played an active role in the ventilation of the gill lamellae. The musculature of the filaments was studied, using visual and electronic methods, and continual muscular activity was noted. Two possible functions of these muscles of the gill filaments have been proposed. Secondly, the brain centres which initiate and maintain the respiratory rhythm were investigated. The neural mechanism was found to be much more complex than had hitherto been suspected in the literature.
Keywords: teleost respiration; gill filament musculature